Expression of human interferon genes using the recA promoter of Escherichia coli. - Feinstein, S I (1983)
Interferon beta 1 and three alpha-interferon genes were cloned on Eco RI fragments isolated from a human genomic library into the Eco RI site of a plasmid containing the recA promoter of E. coli. Expression of interferon activity from cells carrying these plasmids was nalidixic acid inducible. The alpha-interferon genes were expressed only when in the same transcriptional orientation as the recA promoter while the beta 1 interferon gene was expressed in either orientation. Interferon activity was also inducibly expressed from the recA promoter in cells containing a plasmid carrying a fusion of the recA gene with the beta 1 interferon gene. This interferon activity was thirty-fold less sensitive to neutralization by polyclonal antibodies than authentic interferon, implying that the change near the amino terminus affects either antibody recognition or specific activity or both.